Drilling fluids based on a derivative of Malaysian palm oil - Samsuri, Ariffin (1993)
This paper describes a development in the technology of fluids used for drilling oil and gas wells. The development relates to the use of novel fluids based on a Malaysian palm oil derivative as an alternative to oil based drilling fluids.The advantages of using oil based drilling fluids are well documented. However, there is increasing awareness of the serious environmental problems associated with these fluids. This has led to restrictions on the use of oil based drilling fluids in many parts of the world. The ultimate objective must be to eliminate the use of diesel and mineral oil based drilling fluids. There have been significant developments in the technology of water based drilling fluids but there are still many situations where the properties of oil based drilling fluids are required. The Malaysian palm oil derivative can be used to replace mineral oil in the formulation of oil based drilling fluids. These fluids are technically equivalent to oil based muds but are essentially non-toxic, readily biodegradable and based on a renewable raw material that is available locally and in large quantities. The chemistry of the palm oil derivative is described in comparison to that of diesel and mineral oils. Studies on the environmental impact of oil based drilling fluids cuttings are discussed. Biodegradation data is presented which indicates that sea bed recovery should be much more rapid using palm oil drilling fluids than conventional oil based drilling fluids. The formulation and properties of the new fluids are describes with some emphasis on their ability to withstand contamination. It is concluded that fluids based on Malaysian palm oil will form effective alternatives to diesel and mineral oil based drilling fluids in many situations.